2021
DOI: 10.14814/phy2.15125
|View full text |Cite
|
Sign up to set email alerts
|

Aging exaggerates blood pressure response to ischemic rhythmic handgrip exercise in humans

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Autonomic nervous system (ANS) regulates heart activity during exercise using signals from the central nervous system ( Williamson et al, 2006 ) and feedback mechanisms from the exercise pressor reflex (group III and IV muscle afferents) ( Kaufman and Hayes, 2002 ) and the arterial baroreflex, which controls blood pressure and consequently cardiac output ( Charkoudian et al, 2005 ). Previous studies have shown that exercise pressor reflex is impacted by aging ( Caron et al, 2018 ; Trinity et al, 2018 ; Hasegawa et al, 2021 ; Teixeira and Vianna, 2022 ), which would potentially alter the interconnection between the motor and cardiac systems. Nevertheless, the effect is still controversial and further research is needed to fully understand this interconnection pathway, which, in the current study, was quantified through CCM parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Autonomic nervous system (ANS) regulates heart activity during exercise using signals from the central nervous system ( Williamson et al, 2006 ) and feedback mechanisms from the exercise pressor reflex (group III and IV muscle afferents) ( Kaufman and Hayes, 2002 ) and the arterial baroreflex, which controls blood pressure and consequently cardiac output ( Charkoudian et al, 2005 ). Previous studies have shown that exercise pressor reflex is impacted by aging ( Caron et al, 2018 ; Trinity et al, 2018 ; Hasegawa et al, 2021 ; Teixeira and Vianna, 2022 ), which would potentially alter the interconnection between the motor and cardiac systems. Nevertheless, the effect is still controversial and further research is needed to fully understand this interconnection pathway, which, in the current study, was quantified through CCM parameters.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether this is due to alterations in the exercise pressor reflex is inconclusive. Several studies suggest that aging may augment the BP response to exercise (Trinity et al, 2018;Hasegawa et al, 2021). Frontiers in Physiology frontiersin.org Specifically, Hasegawa et al reported that healthy older subjects had a significantly higher systolic BP response to ischemic handgrip exercise compared to that in middle-age and young subjects, and proposed increased sensitivity of the exercise pressor reflex as a possible cause (Hasegawa et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that aging may augment the BP response to exercise ( Trinity et al, 2018 ; Hasegawa et al, 2021 ). Specifically, Hasegawa et al reported that healthy older subjects had a significantly higher systolic BP response to ischemic handgrip exercise compared to that in middle-age and young subjects, and proposed increased sensitivity of the exercise pressor reflex as a possible cause ( Hasegawa et al, 2021 ). Conversely, other studies have shown that healthy older subjects had an attenuated BP response to progressive ischemic handgrip exercise compared to that in younger subjects ( Markel et al, 2003 ), suggesting an attenuated metaboreflex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to conflicting findings, the effects of aging, independent of pathology and physical activity levels, on the exercise pressor reflex are unclear and controversial. Indeed, reports have suggested that the BP response to reflex activation is blunted (Markel et al, 2003), preserved (Ng et al, 1994;Momen et al, 2004;Houssiere et al, 2006;Roseguini et al, 2007;Greaney et al, 2013;Sidhu et al, 2015), or exaggerated (Choi et al, 2012;Schneider et al, 2018;Hasegawa et al, 2021;Wenner et al, 2022). Thus, this review aims to address these discrepant findings and provide a brief overview of the current understanding of the influence of aging on the cardiovascular responses to exercise, focusing on the role of the exercise pressor reflex and proposing future directions for this critical area of research.…”
Section: Introductionmentioning
confidence: 99%